Badiou, Balibar, Rancière : rethinking emancipation - Hewlett, Nick (Continuum studies in continental philosophy., 2007)
In recent years there has been increased interest in three contemporary French philosophers, all former students of Louis Althusser and each now an influential thinker in his own right. Alain Badiou is one of the most important living continental thinkers, well-known for his pioneering theory of the Event. Etienne Balibar has forged new approaches to democracy, citizenship and what he describes as 'equaliberty'. Jacques Rancière has crossed boundaries between history, politics and aesthetics and his work is beginning to receive the attention it deserves. Nick Hewlett brings these three thinker.